Upaya Pencegahan Terorisme di Provinsi Riau (Studi Kasus Ditreskrimum Polda Riau) - Silvi Dwi Rama (UIR PRESS, 2017)
Terrorism is a transnational crime most feared by the world, not to mention Indonesia. Already many who became victims of terrorism crimes one of the tragedy is the bom Bali that link hundreds of souls. In Indonesia, especially in Riau continue to spread terrorism prevention efforts so terrorism crime does not occur in Riau Province. Prevention needs to be done considering the province of Riau began as a transit area of ​​terrorism because it is a region. The purpose of this research is to know what is done by Ditrekrimum Polda Riau in doing prevention of terrorism.The research conducted on Polda Riau which is located at Jalan Jenderal Sudirman no. 215 Pekanbaru, with the subject of research is Ditreskrimum Polda Riau and the result of his research is the prevention of terrorism in Riau Province by Ditreskrimum Polda Riau. The method used is qualitative research method with data technique is interview, observation and documentation. Data analysis using qualitative descriptive method. In this research the informant is Kasubdit 1 State Security Ditreskrimum Polda Riau and Kanit III Subdit 1 Ditreskrimum Polda Riau, as well as one member subdit I Ditreskrimum Polda Riau, as a complementary informant to support the research information. From the results of the research can be concluded that the efforts of terrorism have fulfilled the concept of (Darmawan, 2013). Prevention, prevention, prevention, prevention, prevention, prevention, mitigation, and repressive or arrest measures. In doing the prevention of Polda Riau Ditreskrimum also have conformity with awareness to other society, less effective performance of RT / RW area in which become target of terrorist is difficult to access area.